Pengaruh Supervisi Dan Kualitas Pelayanan Terhadap Kepuasan Siswa Di Lembaga Pendidikan Smect Sains Medan - Bernard V.O. Sirait (Jurnal Manajemen Dan Akuntansi Medan, 2019)
Trade world competition today was really strict. The company was demand to compete with safe in order to get vision and mission of the company which is planned. Supervision to the occupation agent and the job that done, also operate with a good quality service was two things that should have by a company, to reach the main goal of the company it self. Achieving the goal of the company would make that company will be able to survive in the middle of the highest competition of the trade in Indonesia, especially in Medan Island. The purpose that achieve by doing this research was is supervision and service quality significantly influencing toward student’s satisfaction to guidance institution of SMECT Sains Medan, even in partial or simultaneously. Population of the research was all of students of SMECT Sains Medan with amount 168 people, from the population the researcher took sample that used in this research as respondent. Even, the technique of sampling was used simple random sampling. In used Slovin’s formula then the researcher got the amount of sampling as many as 116 students. The method of data accumulation was done by angket. Data analysis that the researcher used was double linier regression by used SPSS program. The result of the research shows that supervision given and quality service was influenced toward students’ satisfaction in partial or simultaneously, even percentage of coefficient of determination (R2) was 0,250 or 25% even the others influenced by motivation and coaching as 25%, even the other was influenced unrevealed variable.